Homeopathic Sulphur Ointment as Adjuvant in the Treatment of Sheep with Myiasis by Cochliomyia hominivorax (Diptera: Calliphoridae): A Case Series - Barros, Giuliano Pereira de; Leme, Denise Pereira; Avilés, Laura Livia Arias; Bricarello, Patrizia Ana (Homeopathy, 2023)
Background Myiasis by Cochliomyia hominivorax (Diptera: Calliphoridae) is a serious problem in animal health. Homeopathic Sulphur presents similarity with the clinical presentation verified in these cases and has already shown in vitro efficacy on the blowfly that causes this pathology. This article presents the report of a series of clinical cases of myiasis by C. hominivorax in sheep that underwent adjuvant treatment with homeopathic Sulphur and presents a theoretical-scientific discussion of biological events related to the clinical treatment of the condition.Patients Seven naturally occurring myiases affecting sheep from an experimental farm were treated by an ointment impregnated with the homeopathic medicine Sulph 12cH, used as adjuvant after the manual removal of accessible larvae from the wound during wound cleaning. The animals were treated daily and evaluated clinically until complete healing of the lesions. Clinical information on the evolution of the inflammatory and scarring process was collected. Blood counts and bacteriological examinations were performed before and after topical homeopathic treatment.Results The homeopathic ointment Sulph 12cH was able to inhibit the development of parasitic C. hominivorax larvae and promote tissue repair and healing in naturally occurring myiasis in the sheep of this study.Conclusion The homeopathic medicine Sulphur, formulated as an ointment, may be a useful new and adjuvant therapeutic option for treating myiasis in animals.
Keywords: myiasis; wound healing; inflammatory process; bacterial resistance; susceptibility to antibiotics